Development of an in vitro Dual Culture System for Grapevine and Xiphinema index as a Tool for Virus Transmission - Winterhagen, P.; Brendel, G.; Krczal, G.; Reustle, G.M. (South African Journal of Enology and Viticulture, 2016)
Grapevine fanleaf virus (GFLV) is a nepovirus that is transmitted to grapevines by the ectoparasitic nematode Xiphinema index. GFLV causes severe losses in yield and quality in viticulture worldwide. Presently, laborious and time-consuming field trials or greenhouse tests are necessary for screening putative GFLV resistance in new grape genotypes developed in breeding programmes. We developed an in vitro dual culture system for grapevines and nematode vectors that requires less time and space than inoculation experiments done in the greenhouse. Virus infection of in vitro grapevines was investigated using immunocapture-reverse transcriptase-polymerase chain reaction (IC-RT-PCR) analysis. The development of root galls induced by feeding nematodes on in vitro grapevines was also analysed. Virus infection in grapevines in the dual culture with viruliferous nematodes was detected six weeks post-inoculation. Root galls were always absent from parasitised in vitro grapevines with detectable virus infection, whereas they developed on some parasitised, but virus-negative tested grapevines. Therefore, root galls cannot be used as a reliable indicator for parasitism and virus transmission.